Sealant composition

By using sealant compositions of polylithium silicate and other additives, the problem of chromium-free corrosion protection on high copper-aluminum alloys is solved, providing excellent corrosion resistance and paint adhesion, meeting the performance requirements of military specifications.

CN120265725APending Publication Date: 2025-07-04HENKEL KGAA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380081379.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-08
Filing Date
2023-10-25
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The prior art has difficulty meeting the corrosion resistance requirements of the military specification MIL-DTL-81706B Class 1A without using hexavalent chromium, especially on aluminum alloys with high copper content, and existing alternatives do not perform well in corrosion protection and paint adhesion.

Method used

Using a sealant composition comprising polylithium silicate, corrosion inhibitor and adhesion promoter, a sealant layer containing lithium, silicon, carbon and oxygen is formed by contacting the converted-coated metal surface to provide corrosion resistance and paint adhesion.

Benefits of technology

Under the conditions without chromium, the corrosion resistance and paint adhesion of aluminum alloys are significantly improved, meeting or close to the performance requirements of the military Class 1A specification, and are easy to operate and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120265725A_ABST
    Figure CN120265725A_ABST
Patent Text Reader

Abstract

Provided herein are sealant compositions for imparting unpainted corrosion resistance to metal surfaces, such as aluminum alloys, wherein the sealant compositions may be substantially free of chromium (VI), permanganate, heavy metals, or lanthanide rare earth metals. Advantageously, the sealant composition can provide performance similar to military Class 1A specifications by imparting unexpected corrosion protection, whether painted or unpainted. Also provided herein are methods of imparting corrosion resistance by applying the sealant compositions, as well as metal surfaces, parts, and articles that have been corrosion resistant using the sealant compositions of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to compositions for protecting metal surfaces from corrosion. Background Art

[0002] The aerospace industry currently uses hexavalent chromium pretreatment under paint layers on metal components to obtain desired paint adhesion and corrosion protection. Chromate conversion coatings are highly water-soluble, easy to apply, durable, and inexpensive. In particular, chromate conversion coatings are highly effective because, in addition to providing "active" or "self-healing" corrosion inhibition, they also provide a strong barrier to water, oxygen, and chlorides. However, chromium(VI) is problematic due to safety and environmental concerns, and many chromium-containing chemicals are expected to be more strictly regulated and may be prohibited in some locations.

[0003] The 1A specification of Military Specification (MIL-DTL-81706B) requires "bare" (unpainted) corrosion resistance on AA2024-T3 alloy and AA7075-T6 alloy after 336 hours of ASTM B117 neutral salt spray testing (showing ≤ 15 pits on 5 panels; ≤ 5 pits / panel, each panel measured 10 inches × 3 inches × 0.032 inches). The 1A specification of MIL-DTL-81706B also requires painted wet tape adhesion testing performance with no adhesion loss along the scribe line after 24 hours of boiling water immersion and tape adhesion testing. Painted wet adhesion is evaluated according to the MIL-DTL-81706B specification with reference to FED-STD-141D (Method 6301.3).

[0004] After decades of research, there is still no chromium-free alternative for chromium pretreatment that meets the requirements of the 1A class of Military Specification. One technical challenge is to match the self-healing corrosion mechanism of Cr(VI) as closely as possible with different chemicals that do not contain Cr(VI), preferably do not contain chromium. Another technical challenge presented by AA2024-T3 aluminum alloy and AA7075-T6 aluminum alloy used in the aerospace industry is their high copper content used to increase the strength-to-weight ratio (these are mainly used on fuselages and wings under tension). Intermetallic copper acts as a cathodic corrosion site where pitting is initiated. There are no other metal pretreatment applications for evaluating bare metals under such aggressive conditions; most other applications rely on additional paint layers and paint adhesion to obtain corrosion protection.

[0005] M.W. Kendig et al., Corrosion 2003, 59, 379–400; NACE International describes the general trends and examples of chemicals that have been investigated as alternatives to chromate-based coatings. Examples of alternative chemicals / methods that have been investigated and found to be unsuccessful include high-valent transition metal oxyanions, refractory metal oxide precursors, rare earth elements, sol-gel chemicals, alkaline earth metal chemicals and hydrotalcite coatings, corrosion inhibiting pigments, and conductive polymer films (ibid.). As the authors note, "Coating chemistries and technologies for replacing chromate conversion still do not exist. A successful method for replacing chromate in current coating and inhibitor formulations will have to rely on the use of several chemicals designed to synergistically perform the role of the unique Cr(VI) oxyanion." No further guidance is provided on identifying or combining the several chemicals.

[0006] In February 2019, PPG announced that one of its aerospace conversion coatings had met the U.S. military specification MIL-C-81706, Type II, Class 3, Type IV, Method A (composition free of hexavalent chromium; for preventing corrosion in cases where low resistance is required; premixed liquid, thixotropic; spray). The Class 3 specification test was conducted on AA6061-T6 under 168-hour bare salt spray testing conditions. The Class 1A specification test was conducted on AA2024-T3 and AA7075-T6 under 336-hour bare salt spray testing conditions; compared to the Class 3 specification, this is twice the number of hours of bare salt spray testing on the more challenging high-copper aluminum alloys. Currently, there is no commercially available source of chromium-free products that pass the military specification Class 1A specification (maximum corrosion protection, painted or unpainted). SUMMARY OF THE INVENTION

[0007] Disclosed herein is a sealant composition for imparting corrosion resistance to a metal surface, the sealant composition comprising lithium polysilicate, a corrosion inhibitor, an adhesion promoter, and water. Desirably, the sealant composition contains little or no additional chromium other than trace amounts from other raw materials or dissolved from the substrate; preferably, the sealant contains less than 20 ppm of chromium (VI).

[0008] Also disclosed is a method for protecting a metal surface, the method comprising contacting a conversion-coated metal surface with a sealant composition according to the present disclosure.

[0009] The present disclosure also provides a metal component comprising a surface that has been contacted with a sealant composition according to the present disclosure. Articles are also provided that respectively comprise a metal component that has been contacted with a sealant composition according to the present disclosure.

[0010] Also provided is an article comprising a metal surface on which a conversion coating is deposited, and a sealant layer that is in-situ dried on the conversion coating and contains lithium, silicon, carbon, and oxygen.

[0011] The present disclosure also provides an article comprising a metal surface on which a sealant layer is deposited, and lithium is distributed in the sealant layer in an amount of about 2 - 7 mg / m 2 as measured by glow discharge optical emission spectroscopy (GD - OES).

[0012] In one aspect (Aspect 1) of the present disclosure, there is provided a sealant composition for imparting corrosion resistance to a metal surface, the sealant composition comprising: lithium polysilicate; a corrosion inhibitor; and an adhesion promoter; and water; wherein the sealant composition is substantially free of chromium (VI). Further aspects include:

[0013] Aspect 2: The sealant composition according to Aspect 1, wherein the lithium polysilicate is present in an amount of about 1 - 3 wt% based on the total weight of the composition.

[0014] Aspect 3: The sealant composition according to Aspect 2, wherein the lithium polysilicate is present in an amount of about 1.45 - 2.25 wt% based on the total weight of the composition.

[0015] Aspect 4: The sealant composition according to any one of the preceding aspects, wherein the corrosion inhibitor comprises one or more of quinoline, organophosphates, azolic functional molecules, or any combination thereof.

[0016] Aspect 5: The sealant composition according to any one of the preceding aspects, wherein the corrosion inhibitor comprises 8 - hydroxyquinoline, organophosphates, salicylaldoxime, quinolinic acid, 1H - benzotriazole, tolyltriazole, methyl - 1 - H - benzotriazole, 2 - mercaptobenzothiazole, 2 - mercaptobenzoxazole, 5 - amino - 1,3,4 - thiadiazole - 2 - thiol, L - cysteine, 5 - aminotetrazole, 2 - aminothiazole, or any combination thereof.

[0017] Aspect 6: The sealant composition according to any one of the preceding aspects, wherein the corrosion inhibitor comprises 8 - hydroxyquinoline.

[0018] Aspect 7: The sealant composition according to any one of the preceding aspects, wherein the corrosion inhibitor comprises a C8 - C 16 -alkyl polyethylene glycol ether.

[0019] Aspect 8: The sealant composition according to any one of the foregoing aspects, wherein the corrosion inhibitor comprises a phosphate ester based on lauryl polyethylene glycol ether.

[0020] Aspect 9: The sealant composition according to any one of the foregoing aspects, wherein the corrosion inhibitor is present in an amount of from about 0.005% by weight to the solubility limit of the corrosion inhibitor in the sealant composition, based on the total weight of the composition.

[0021] Aspect 10: The sealant composition according to any one of the foregoing aspects, wherein the composition is alkaline.

[0022] Aspect 11: The sealant composition according to any one of the foregoing aspects, wherein the adhesion promoter comprises an organofunctional alkoxysilane compound.

[0023] Aspect 12: The sealant composition according to any one of the foregoing aspects, wherein the adhesion promoter comprises an alkoxy functional group.

[0024] Aspect 13: The sealant composition according to any one of the foregoing aspects, wherein the adhesion promoter comprises an organofunctional group, the organofunctional group comprising epoxy, epoxyalkyl, epoxyalkoxy, epoxyalkoxy, amino, aminoalkyl, or aminoalkylamino, or any combination thereof.

[0025] Aspect 14: The sealant composition according to any one of the foregoing aspects, wherein the adhesion promoter comprises 3-glycidoxypropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, or 3-glycidoxypropyltrimethoxysilane and N-2-aminoethyl-3-aminopropyltrimethoxysilane.

[0026] Aspect 15: The sealant composition according to any one of the foregoing aspects, wherein, based on the total weight of the composition, the adhesion promoter is present in an amount of about 0.5 - 5% by weight.

[0027] Aspect 16: The sealant composition according to any one of the foregoing aspects, further comprising a surfactant.

[0028] Aspect 17: The sealant composition according to any one of the foregoing aspects, wherein the sealant composition does not contain any metal source other than lithium polysilicate.

[0029] Aspect 18: A method for protecting a metal surface from corrosion, the method comprising contacting a conversion-coated metal surface with a sealant composition according to any one of aspects 1 - 17.

[0030] Aspect 19: The method according to aspect 18, wherein the converted and coated metal surface is immersed in the sealant composition.

[0031] Aspect 20: The method according to aspect 18 or aspect 19, wherein the converted and coated metal surface is contacted with the sealant composition under ambient temperature conditions.

[0032] Aspect 21: The method according to any one of aspects 18 - 20, wherein the metal surface comprises aluminum or an aluminum alloy.

[0033] Aspect 22: The method according to any one of aspects 18 - 21, the method further comprising contacting the metal surface with a conversion coating composition before the step of contacting the metal surface with the sealant composition, wherein the conversion coating composition does not contain any chromium source.

[0034] Aspect 23: The method according to any one of aspects 18 - 22, wherein the conversion coating composition comprises a Group IVB metal.

[0035] Aspect 24: The method according to any one of aspects 18 - 23, wherein the converted and coated metal surface comprises an oxide of a Group IVB metal.

[0036] Aspect 25: The method according to any one of aspects 18 - 24, wherein the conversion coating comprises Zr, Ti, or Zr and Ti.

[0037] Aspect 26: The method according to any one of aspects 18 - 25, the method further comprising a step of deoxidizing the metal surface before the step of contacting the metal surface with the sealant composition.

[0038] Aspect 27: The method according to aspect 26, wherein the step of deoxidizing the metal surface is before contacting the metal surface with the conversion coating composition.

[0039] Aspect 28: The method according to any one of aspects 18 - 27, the method further comprising a step of degreasing the metal surface before the step of contacting the metal surface with the sealant composition.

[0040] Aspect 29: The method according to aspect 28, wherein the step of degreasing the metal surface is before the step of deoxidizing the metal surface and before contacting the metal surface with the conversion coating composition.

[0041] Aspect 30: A metal component, the metal component comprising a surface that has been contacted with the sealant composition according to any one of aspects 1 - 17.

[0042] Aspect 31: The metal component according to aspect 30, wherein the surface comprises aluminum or an aluminum alloy.

[0043] Aspect 32: An article comprising the metal component according to aspect 30 or aspect 31.

[0044] Aspect 33: An article comprising: a metal surface having a conversion coating containing a Group IVB metal deposited thereon, and a sealant layer in-situ dried on the conversion coating and containing Li, Si, C, and O.

[0045] Aspect 34: An article comprising a metal surface having a sealant layer deposited thereon, wherein lithium is distributed in the sealant layer in an amount of about 2 - 7 mg / m 2 as measured by glow discharge optical emission spectrometry (GD - OES). BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1A A flow chart depicting a conventional (chromium - containing) conversion method (comparative) is provided, while Figure 1B a flow chart of a conversion method using a sealant composition according to the present disclosure is provided.

[0047] Figure 2 A GD - OES spectrum of an as - cleaned, de - oxygenated, and uncoated AA2024 aluminum alloy is provided.

[0048] Figure 3 A GD - OES spectrum of an Figure 2 AA2024 aluminum alloy that has been treated with a chromium - free conversion coating bath is provided.

[0049] Figure 4 A GD - OES spectrum of an Figure 3 AA2024 aluminum alloy that has been immersed in an exemplary sealant composition is provided.

[0050] Figure 5 A GD - OES spectrum of an Figure 3 AA2024 aluminum alloy that has been immersed in another exemplary sealant composition is provided.

[0051] Figure 6 A GD - OES spectrum of an Figure 3 AA2024 aluminum alloy that has been immersed in another exemplary sealant composition is provided.

[0052] Figure 7 A GD - OES spectrum of an Figure 3 AA2024 aluminum alloy that has been immersed in another exemplary sealant composition is provided. DETAILED DESCRIPTION

[0053] The inventive subject matter of the present disclosure can be more readily understood by reference to the following detailed description, taken in conjunction with the drawings and examples that form a part of this disclosure. It should be understood that these inventions are not limited to the specific components, methods, or parameters described and / or shown herein, and that the terminology used herein is for the purpose of describing particular embodiments by way of example only and is not intended to limit the claimed inventions.

[0054] The entire disclosure of each patent, patent application, and publication cited or described in this document is hereby incorporated by reference herein.

[0055] As used above and throughout this disclosure, unless otherwise specified, the following terms and abbreviations shall be understood to have the following meanings.

[0056] In this disclosure, unless the context clearly dictates otherwise, the singular forms "a / an" and "the" include plural referents, and reference to a particular numerical value includes at least that particular value. Thus, for example, reference to "a corrosion inhibitor" is a reference to one or more such corrosion inhibitors known to those skilled in the art and their equivalents, etc. Further, when it is stated that an element "may be" X, Y, or Z, such usage is not intended to exclude other alternatives for the element in all instances.

[0057] When a value is expressed as an approximation by use of the antecedent "about", it should be understood that the particular value forms another embodiment. Generally, the use of the term "about" indicates an approximation that may vary depending on the desired properties sought to be obtained by the disclosed subject matter and is to be interpreted in the context in which it is used based on its function. In some embodiments, "about X" (where X is a numerical value) means ±10% (inclusive) of that value. For example, the phrase "about 8" can refer to a value from 7.2 (inclusive) to 8.8 (inclusive). This value can include "exactly 8". Where ranges are provided, all ranges are inclusive and combinable. For example, when listing a range of "1 to 5", the recited range should be interpreted as optionally including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 & 4 to 5", "1 to 3 & 5", etc. Further, when a list of alternative choices is explicitly provided, such a list can also include embodiments in which any one of the recited alternatives can be excluded. For example, when describing a range of "1 to 5", such a description can support cases where any one of 1, 2, 3, 4, or 5 is excluded; thus, the recitation of "1 to 5" can support "1 and 3 to 5, without 2", or simply "where 2 is not included".

[0058] As described above, the aerospace industry and other industries that use metal parts, such as aerospace aluminum alloys, do not have an alternative metal pretreatment application that meets the 1A class requirements of military specifications and represents the widely used chromium pretreatment. The present inventors have unexpectedly discovered a sealant composition for pretreating metal surfaces, including those of aerospace aluminum alloys, that is water-based, alkaline, substantially free of heavy metals, permanganates, and lanthanide metals, and can be operated at ambient temperature with short immersion times. Although individual known chromium-free conversion coatings exhibit little uncoated corrosion resistance (> 100 pitting marks; severe corrosion), application of the sealant composition of the present disclosure significantly enhances corrosion protection without compromising paint adhesion performance. For example, as more fully disclosed herein, when the sealant composition of the present invention is used on aluminum surfaces pretreated with a chromium-free conversion coating, no pitting or white corrosion products are observed after 168 hours (1 week) of neutral salt spray testing of AA2024-T3 aluminum alloy, after 336 hours (2 weeks) of neutral salt spray testing of AA6061-T6 aluminum alloy, and after 240 hours (10 days) of neutral salt spray testing of AA7075-T6 aluminum alloy. In addition, after applying the composition of the present invention to the above-described conversion-coated metal surfaces, the panels are subsequently painted and the adhesion is tested, and the result is that no paint adhesion loss is observed along the scribe lines after 24-hour boiling water immersion and tape adhesion testing, even when a Cr-free primer is used.

[0059] Accordingly, in one embodiment, a sealant composition for imparting corrosion resistance to a metal surface is disclosed herein, the sealant composition comprising lithium polysilicate, a corrosion inhibitor, an adhesion promoter, and water, wherein the sealant composition comprises less than 20 ppm of chromium (VI).

[0060] Based on the total weight of the composition, lithium polysilicate may be provided in an amount of about 1-3 wt%. Lithium polysilicate is commercially available in the form of a 20% (w / w) dilution in water, and the present invention includes compositions that can use this commercial source. Accordingly, the amount of lithium polysilicate is expressed herein relative to the commercially available 20% (w / w) dilution in water. In certain embodiments, lithium polysilicate is present in the composition in an amount of about 1.2-2.75 wt%, about 1.3-2.5 wt%, about 1.4-2.4 wt%, or about 1.45-2.25 wt%. For example, based on the total weight of the composition, lithium polysilicate may be present in an amount of about 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or 3 wt%.

[0061] The corrosion inhibitors that can be in the compositions of the present invention can include nitrogen-containing corrosion inhibitors. The corrosion inhibitors can be, for example, quinoline, organic phosphates, azole-functional molecules, or any combination thereof. Azole-functional molecules can include, for example, diazoles, triazoles, tetrazoles, etc., and such molecules can optionally also contain oxygen, sulfur, or both oxygen and sulfur. The organic phosphates can be straight-chain, branched, saturated, or unsaturated fatty alcohol phosphates. For example, the organic phosphate can be a C4-C 26 alkyl polyethylene glycol ether, including C4-C 26 alkyl polyethylene glycol ether, C8-C 16 alkyl polyethylene glycol ether, or C 10 -C 14 alkyl polyethylene glycol ether, such as straight-chain or branched polyethylene glycol ethers, including polyalkoxylated phosphates, and preferably phosphates based on lauryl polyethylene glycol ether. Other examples of corrosion inhibitors that can be used in the compositions of the present invention include 8-hydroxyquinoline, organic phosphates, fatty acid alkoxylated phosphates, phosphates based on lauryl polyethylene glycol ether, salicylaldoxime, quinolinic acid, 1H-benzotriazole, tolyltriazole, methyl-1-H-benzotriazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, 5-amino-1,3,4-thiadiazole-2-thiol, L-cysteine, 5-aminotetrazole, 2-aminothiazole, or any combination thereof.

[0062] The corrosion inhibitor (which can be two or more corrosion inhibitors) can be present in the sealant composition in an amount of about 0.005 wt% to the solubility limit of the corrosion inhibitor, based on the total weight of the composition. In certain instances, based on the total weight of the composition, the corrosion inhibitor is present in an amount of about 0.005 - 0.2 wt%, such as in an amount of about 0.005, 0.01, 0.015, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.125, 0.15, 0.175, or 0.2 wt%.

[0063] The adhesion promoter of the compositions of the present invention can be, for example, an organofunctional alkoxysilane compound. The alkoxy functional groups in such compounds can be methoxy, ethoxy, propoxy, or any combination thereof. The organofunctional groups in the adhesion promoter compound can include, for example, epoxy groups, epoxyalkyl groups, epoxyalkoxy groups, epoxyalkoxy groups, amino groups, aminoalkyl groups, or aminoalkylamino groups, or any combination thereof.

[0064] Exemplary epoxy silanes include, but are not limited to: glycidyloxy methyltrimethoxysilane, 3-glycidyloxypropyltrihydroxysilane, 3-glycidyloxypropyldimethylhydroxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyldimethoxymethylsilane, 3-glycidyloxypropyldimethylmethoxysilane, 3-glycidyloxypropyltributoxysilane, 1,3-bis(glycidyloxypropyl)tetramethyldisiloxane, 1,3-bis(glycidyloxypropyl)tetramethoxydisiloxane, 1,3-bis(glycidyloxypropyl)-1,3-dimethyl-1,3-dimethoxydisiloxane, 2,3-epoxypropyltrimethoxysilane, 3,4-epoxybutyltrimethoxysilane, 6,7-epoxyheptyltrimethoxysilane, 9,10-epoxydecyltrimethoxysilane, 1,3-bis(2,3-epoxypropyl)tetramethoxydisiloxane, 1,3-bis(6,7-epoxyheptyl)tetramethoxydisiloxane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and the like.

[0065] Any suitable amino silane can be used. In some embodiments, the amino silane is a polyfunctional amino silane, such as a silane having two or more amino groups per molecule. While any suitable amino silane can be used, examples of suitable amino silanes include, but are not limited to: the monoamine-functional 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane, the diamine-functional (functionally containing both secondary and tertiary amines) 2-aminoethyl-3-aminopropyltrimethoxysilane (also known as "DAMO"), and the secondary amine-functional n-butylaminopropyltrimethoxysilane and n-ethylaminoisobutyltrimethoxysilane.

[0066] In some embodiments, the adhesion promoter includes 3-glycidyloxypropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, or 3-glycidyloxypropyltrimethoxysilane and N-2-aminoethyl-3-aminopropyltrimethoxysilane.

[0067] Based on the total weight of the composition, the amount of the adhesion promoter in the sealant composition of the present invention can be about 0.5 - 5 wt%. For example, based on the total weight of the composition, the amount of the adhesion promoter can be about 0.6 - 4 wt%, 0.65 - 4 wt%, 0.7 - 4 wt%, or 0.7 - 0.35 wt%, such as about 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, or 5 wt%.

[0068] The sealant composition may further comprise a surfactant. The surfactant can be ionic or anionic. The surfactant can be, for example, an alkoxylated alcohol surfactant (e.g., secondary alcohol ethoxylate, which can be ionic or preferably anionic) or a sulfosuccinate anionic surfactant. Exemplary surfactants include Tergitol 15 - S - 7 (secondary alcohol ethoxylate) nonionic surfactant. Other compatible surfactants include, but are not limited to, Aerosol OT - 70PG or Aerosol WA - 300 (diester sulfosuccinate) anionic surfactants and ECOSURF EH - 9 (secondary alcohol ethoxylate) nonionic surfactant.

[0069] The sealant composition is preferably alkaline. For example, the pH of the composition can be in the range of 8 - 14, such as 9 - 12 or 9.5 - 11.

[0070] The sealant composition according to the present disclosure is free or substantially free of chromium (VI) and can thus meet the requirements of the REACH regulation, while improving the corrosion performance compared to a separate chromium - free conversion coating and approaching the performance similar to military specification 1A class by imparting unexpected corrosion protection (whether painted or unpainted). As used herein, when referring to the composition of the present invention, "substantially free of chromium (VI)" can mean that the composition contains less than 20 ppm of chromium (VI). In some embodiments, the composition contains less than 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 ppm of chromium (VI). In certain embodiments, the composition is free of any chromium (VI).

[0071] The sealant compositions according to the present disclosure may also be substantially free of chromium (III). As used herein, when referring to the compositions of the present invention, "substantially free of chromium (III)" may mean that the composition contains less than 20 ppm of chromium (III). In some embodiments, the composition contains less than 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 ppm of chromium (III). In certain embodiments, the composition is free of any chromium (III).

[0072] Preferably, the sealant compositions of the present invention do not provide chromium (VI) or chromium (III) to the conversion coating systems in which they are used (except for the chromium (VI) or chromium (III) they would provide when determined to be substantially free of chromium (VI) and chromium (III) as detailed above), and the chromium (VI) or chromium (III) present in the conversion coating systems (to which the compositions of the present invention are applied) is only trace amounts derived from the raw materials used, the substrates being treated, or trace elements in the water. For example, aluminum alloys themselves can contain chromium (VI): alloy AA2024-T3 contains 0.01% (100 ppm) Cr, alloy AA6061-T6 contains 0.18% Cr (1800 ppm), and alloy AA7075-T6 contains 0.19% Cr (1900 ppm). The current federal drinking water standard for total chromium (including chromium (VI) and chromium (III)) is 0.1 mg / L (0.1 ppm / 100 ppb / 0.00001% Cr). Compared to the compositions of the present invention, the working bath of BONDERITE M-CR T 5900 contains 0.053% Cr (530 mg / L or 530 ppm) (see U.S. Publication No. 2017 / 0009330, incorporated herein by reference).

[0073] In certain embodiments, the sealant compositions of the present invention are free of any source of permanganate, heavy metals, or rare earth metals. Preferably, the only source of metal within the sealant composition is the alkali metal lithium introduced via lithium polysilicate. Thus, in some embodiments, the sealant composition is substantially free of permanganate, heavy metals, or rare earth metals, which is intended to mean that the composition contains less than 20 ppm of any one of permanganate, heavy metals, or rare earth metals (i.e., less than 20 ppm of permanganate, less than 20 ppm of heavy metals, and less than 20 ppm of rare earth metals). In some embodiments, the composition contains less than 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 ppm of permanganate, heavy metals, or rare earth metals, respectively. In certain embodiments, the composition is free of any permanganate. In certain embodiments, the composition is free of any heavy metals. In certain embodiments, the composition is free of any rare earth metals.

[0074] Also provided herein is a method for protecting a metal surface from corrosion, the method comprising contacting a conversion-coated metal surface with a sealant composition according to any one of the embodiments disclosed above. The metal surface can be the surface of any metal piece, component, or part that requires corrosion protection, which includes, for example: steel, aluminum and its alloys, zinc and its alloys, and metals plated with zinc, aluminum, and their alloy layers, and (a mixture comprising aluminum, zinc, and silicone). In a preferred embodiment, the metal surface is the surface of an aluminum alloy. Aluminum alloys commonly used in aerospace applications include AA2024-T3, AA6061-T6, and AA7075-T6, any of which can be used according to the method of the present invention. The metal surface is conversion-coated according to conventional methods, but preferably using a chromium-free method. For example, the conversion coating method can include contacting the metal surface with a composition comprising a Group IVB metal, thereby producing a conversion-coated metal surface comprising an oxide of the Group IVB metal. Exemplary Group IVB metal components of the conversion coating include Zr, Ti, or Zr and Ti.

[0075] The step of contacting the conversion-coated metal surface with the sealant composition can be accomplished by any conventional means. Preferably, the conversion-coated metal surface is immersed in the sealant composition. An advantageous feature of the method of the present invention is that the step of contacting the conversion-coated metal surface with the sealant composition can be carried out under ambient temperature conditions. For example, the temperature at which the contacting step occurs can be about 67 - 78°F.

[0076] Figure 1A A flow chart of a conventional (chromium) conversion method for a metal surface is provided. In step 5, a chromium conversion coating is applied to the metal.Figure 1B A flowchart of an exemplary conversion method according to the present disclosure is provided, where a chromium-free conversion coating is used in step 5 and the sealant composition of the present invention is applied in step 8.

[0077] The method of the present invention may also include additional conventional steps related to the conversion coating method. For example, the method may also include a step of deoxidizing the metal surface before the step of contacting the metal surface with the sealant composition. The method may include a step of degreasing the metal surface before the step of contacting the metal surface with the sealant composition. The step of degreasing the metal surface is preferably before the step of deoxidizing the metal surface and before the step of contacting the metal surface with the conversion coating composition.

[0078] An exemplary method for imparting corrosion resistance to a metal component according to the present disclosure can be carried out using steps 1-9 provided as follows:

[0079] - Step 1 (cleaning bath): Perform aqueous alkaline degreasing with 20% (v / v) and 60 °C C-AK 6849 for 15 minutes.

[0080] - Step 2 (tap water rinse): Rinse with warm tap water for 5 minutes.

[0081] - Step 3 (deoxidizing bath): Perform acid deoxidation with 15% (v / v) C-IC 2310 + 25% (v / v) HNO3 at ambient temperature for 5 minutes (etching rate of clad plate = 0.1 - 0.4 mils / surface / hour).

[0082] - Step 4 (tap water rinse): Rinse with ambient tap water for 2 minutes.

[0083] - Step 5 (Cr-free conversion coating): M-NT 1820 (without copper additive; 3% v / v;

[0084] pH = 4.4 - 4.6; free fluoride = 50 ppm) at ambient temperature for 10 minutes (accompanied by agitation by magnetic stirring at 300

[0085] rpm).

[0086] - Step 6 (deionized water rinse): Rinse with ambient deionized water for 2 minutes.

[0087] - Step 7 (air drying): Air dry at ambient temperature for 10 minutes.

[0088] - Step 8 (Cr-free sealant): The sealant bath composition at ambient temperature for 2 minutes (accompanied by agitation).

[0089] - Step 9 (air drying): Air dry at ambient temperature.

[0090] The present disclosure also provides metal components, each of which includes a surface that has been contacted with the sealant composition according to any one of the above-described embodiments. The surface can be the surface of any metal piece, component, or part that requires corrosion protection, including, for example, steel, aluminum and its alloys, zinc and its alloys, and metals plated with layers of zinc, aluminum, and their alloys, and (a mixture comprising aluminum, zinc, and silicone). In a preferred embodiment, the metal surface is the surface of an aluminum alloy. Aluminum alloys commonly used in aerospace applications include AA2024-T3, AA6061-T6, and AA7075-T6, and any of these can be used according to the method of the present invention.

[0091] The present disclosure also provides an article including a metal component, the metal component including a surface that has been contacted with the sealant composition according to any one of the above embodiments. The metal component can be according to any of the embodiments described in the immediately preceding paragraph. An article according to the present disclosure can be, for example, an aircraft or a component thereof, such as a wing, fuselage, engine housing, propeller, tail, fin, aileron, door, antenna, strut, etc.

[0092] The present disclosure also provides an article including a metal surface on which a conversion coating is deposited, and a sealant layer, the conversion coating comprising, for example, a Group IVB metal, the sealant layer drying in situ on the conversion coating and comprising Li, Si, C, and O. Exemplary Group IVB metal components of the conversion coating include Zr, Ti, or Zr and Ti. In some embodiments, the conversion coating comprises Zr and oxygen. The sealant layer is preferably substantially free of chromium (VI), substantially free of chromium (III), or substantially free of both chromium (VI) and chromium (III). The metal surface can be the surface of any metal piece, component, or part that requires corrosion protection, including, for example: steel, aluminum and its alloys, zinc and its alloys, and a substrate having a coating of aluminum or zinc and its alloys (e.g., ). In a preferred embodiment, the metal surface is the surface of an aluminum alloy. Aluminum alloys commonly used in aerospace applications include AA2024-T3, AA6061-T6, and AA7075-T6, and any of these can be included in the articles of the present disclosure.

[0093] In another embodiment, an article is provided that includes a metal surface on which a sealant layer is deposited, and lithium is distributed in the sealant layer in an amount of about 2-7 mg / m as measured by glow discharge optical emission spectrometry (GD-OES) 2 For example, lithium can be present in an amount of about 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, or 7 mg / m as measured by GD-OES 2The amount is distributed within the sealant layer. As described above, the sealant composition disclosed in the present invention comprises lithium polysilicate, and the sealant layer produced by applying the sealant composition of the present invention to a metal surface can thus contain lithium at the above concentrations.

[0094] Example

[0095] The present invention is further defined in the following examples. It should be understood that, although these examples show preferred embodiments of the present invention, they are given by way of illustration only and should not be construed as limiting the appended claims. From the above discussion and these examples, those skilled in the art can determine the basic features of the present invention and, without departing from its spirit and scope, can make various changes and modifications to adapt it to various uses and conditions.

[0096] Example 1 - Table of Exemplary Sealant Compositions and Conversion Coating Compositions

[0097] The following Table 1 provides ranges of components and conditions for exemplary sealant compositions according to the present disclosure.

[0098] Table 1

[0099] Parameter Range Narrower range Lithium polysilicate (20 wt% dilution) 1-3% 1.45-2.25% 3-Glycidoxypropyltrimethoxysilane 0.3-2% 0.35-1.75% N-2-Aminoethyl-3-aminopropyltrimethoxysilane 0.3-2% 0.35-1.75% 8-Hydroxyquinoline 0.005-0.10% 0.015-0.050% Phosphate ester based on lauryl polyethylene glycol ether 0.005-0.20% 0.010-0.150% pH 9.8-11 10-10.8

[0100] The following Table 2 provides ranges of components and conditions for exemplary conversion coating compositions that can be used to prepare metal surfaces to be treated with the sealant composition of the present invention.

[0101] Table 2

[0102] Parameter Range Narrower range Zirconium 50 - 750 ppm 100 - 200 ppm Nitrate > 3500 ppm 4000 - 8000 ppm pH 3.6-4.8 3.8-4.6 Free fluoride 10 - 80 ppm 15 - 75 ppm

[0103] Example 2 - Sealant Composition and Its Application and Testing

[0104] To prepare a 700 g sealant bath, 10.41 g (1.49%) of lithium polysilicate (20%) was stirred into 684.14 g of deionized water. To this solution was added 2.63 g (0.375%) of GLYMO (3-glycidoxypropyltrimethoxysilane) obtained from Evonik. Then, the solution was stirred for at least 30 minutes to ensure complete dissolution of GLYMO. Subsequently, 2.63 g (0.375%) of DAMO (N-2-aminoethyl-3-aminopropyltrimethoxysilane) was added and the solution was stirred for 10 minutes. 0.19 g (0.027%) 8-hydroxyquinoline was added to the solution and the solution was stirred for 1 hour to ensure that the 8-hydroxyquinoline was completely dissolved (pH = 10.16). Table 3 below provides an overview of the components of the sealant composition.

[0105] Table 3

[0106]

[0107] Q-Lab AA2024-T3 aluminum panels (3" x 10" x 0.032") were immersed in an aqueous alkaline degreaser bath (20% v / v and 60°C) with constant agitation. C-AK 6849) for 15 minutes. The panels were then immersed in a warm tap water rinse tank for 5 minutes and then immersed in an acidic deoxidation bath (15% v / v C-IC 2310 + 25% v / v HNO3, ambient temperature) for 5 minutes (etch rate for cladding plate = 0.1-0.4 mil / surface / hour). After deoxidation, the plates were immersed in an ambient tap water rinse tank for 2 minutes and then immersed in a 1% tantalum bath containing 1% tantalum at ambient temperature while being agitated by magnetic stirring at 300 rpm. The panels were then immersed in a "Cr-free conversion coating" of M-NT 1820 (no copper additive; 3% (v / v); pH = 4.2-4.4; free fluoride = 50 ppm) for 10 minutes. After conversion coating, the panels were immersed in an ambient deionized water rinse tank for 2 minutes, and then air-dried at ambient temperature for 10 minutes. Next, the panels were immersed in the above sealant bath for 2 minutes at ambient temperature with slight agitation, and then air-dried at ambient temperature before performance evaluation.

[0108] The corrosion performance of the treated substrates was evaluated after 7 days (168 hours) of neutral salt spray testing (ASTM B117) according to the MIL-DTL-81706B specification. Paint wet adhesion was evaluated according to the MIL-DTL-81706B specification with reference to FED-STD-141D (Method 6301.3) to obtain the test parameters. The panels were coated with a chromate-based primer (MIL-PRF-23377K, Type 1, Class C2; 23377F12-GL). Table 4 below provides the results of the corrosion performance evaluation. Test results from unsealed samples are provided in Table 5.

[0109] Table 4

[0110] Sample Corrosion rating on AA2024 (168-hour NSS) Adhesion rating on AA2024 1 1 corrosion spot; almost no white corrosion products Negligible (almost no) paint peeling 2 No corrosion spots; no white corrosion products Negligible (almost no) paint peeling 3 2 corrosion spots; a small amount of white corrosion products Qualified (no paint peeling)

[0111] Table 5

[0112]

[0113] Example 3 - Sealant Composition and Its Application and Testing

[0114] To prepare a 700 g sealant bath, 10.41 g (1.49%) of lithium polysilicate (20%) was stirred into 668.40 g of deionized water. To this solution was added 10.50 g (1.5%) of GLYMO (3 - glycidoxypropyltrimethoxysilane) obtained from Evonik. Then, the solution was stirred for at least 30 minutes to ensure complete dissolution of GLYMO. Next, 10.50 g (1.5%) of DAMO (N - 2 - aminoethyl - 3 - aminopropyltrimethoxysilane) obtained from Evonik was added, and the solution was stirred for 10 minutes. To the solution was added 0.19 g (0.027%) of 8 - hydroxyquinoline, and the solution was stirred for 1 hour to ensure complete dissolution of 8 - hydroxyquinoline (pH = 10.24). Table 6 below provides an overview of the components of the sealant composition.

[0115] Table 6

[0116]

[0117] Q - Lab AA2024 - T3, AA6061 - T6, and AA7075 - T6 aluminum plates (3”×10”×0.032”) were immersed in an aqueous alkaline degreasing bath (20% (v / v) and 60 °C C - AK 6849) with continuous agitation for 15 minutes. Then, the plates were immersed in a warm tap water rinse tank for 5 minutes, and then in an acidic deoxidizing bath (15% (v / v) C - IC 2310 + 25% (v / v) HNO3, ambient temperature) for 5 minutes (etching rate of clad plates = 0.1 - 0.4 mils / surface / hour). After deoxidation, the plates were immersed in an ambient temperature tap water rinse tank for 2 minutes, and then at ambient temperature while being agitated by magnetic stirring at 300 rpm, they were immersed in a “Cr - free conversion coating” containing M - NT 1820 (without copper additive; 3% (v / v); pH = 4.2 - 4.4; free fluoride = 50 ppm) for 10 minutes. After conversion coating, the plates were immersed in an ambient temperature deionized water rinse tank for 2 minutes, and then air - dried at ambient temperature for 10 minutes. Next, the plates were immersed in the above - mentioned sealant bath at ambient temperature with slight agitation for 2 minutes, then air - dried at ambient temperature, and then subjected to performance evaluation.

[0118] After a 7-day (168-hour) neutral salt spray test (ASTM B117) conducted in accordance with the MIL-DTL-81706B specification, the corrosion performance of the treated substrate is evaluated. The wet paint adhesion is evaluated in accordance with reference FED-STD-141D (method 6301.3) for the MIL-DTL-81706B specification to obtain the test parameters. The panels are coated with a chromate-based primer (MIL-PRF-23377K, type 1, class C2; 23377F12-GL) and / or a non-chromate primer (MIL-PRF-23377REV K, type 1, class N primer, epoxy high solids; 02GN084 Deft Light Aqua Green). Table 7-8 below provides the results of the corrosion performance evaluation for each of the tested samples.

[0119] Table 7

[0120] Sample Corrosion rating on AA2024 Adhesion rating on AA2024 4 No corrosion spots; no white corrosion products Negligible (almost no) paint peeling 5 2 corrosion spots; a small amount of white corrosion products Negligible (almost no) paint peeling

[0121] Table 8

[0122]

[0123] Example 4 - Comparative Evaluation

[0124] Pre-treatment systems based on permanganate and / or cerium conversion coatings with a lithium-containing sealant layer disclosed in U.S. Publication Nos. 2016 / 0083849 and 2019 / 0316261 (both incorporated herein by reference) are screened for comparative evaluation. The best-performing examples disclosed in these publications are reproduced. The panels are treated with a first-stage conversion coating bath solution and then with a second-stage coating bath. The first-stage conversion coating bath solution contains: (1) sodium permanganate; (2) a mixture of sodium permanganate and cerium nitrate; or (3) a mixture of yttrium nitrate, cerium nitrate, cerium chloride, and hydrogen peroxide. The second-stage coating bath contains (1) lithium carbonate or (2) a mixture of lithium carbonate and benzotriazole. The above-cited published patent applications indicate that AA2024-T3 panels immersed in the conversion coating bath at room temperature for 2 minutes (permanganate-based bath) or 5 minutes (yttrium-based bath) and after a 4-day (96-hour) neutral salt spray test (in accordance with ASTM B117) look substantially the same as they did at the start of the test. Repeat the disclosed variations as described in the publications.

[0125] Results. Using Plates treated with M-NT 1820 analog (without Cu) and sealed with a bath containing lithium carbonate showed a significant amount of paint peeling after the painted wet adhesion test. All other plates showed acceptable painted wet adhesion or negligible paint peeling. Plates treated with yttrium nitrate and cerium nitrate barrier layers and sealed with a bath containing lithium carbonate exhibited significant pitting and white corrosion products. Plates treated with permanganate barrier layers and sealed with a bath containing lithium carbonate started the test in a uniform golden to dark brown color. After the neutral salt spray test, most of these plates were brown / green rainbow-colored with fine shiny stripes. The plates showed very little white corrosion product, and pitting preferentially occurred within the shiny stripes. With Plates treated with M-NT 1820 analog (without Cu) and sealed with a bath containing lithium carbonate showed some pitting (~10 pits) and a moderate amount of white corrosion product. However, with Plates treated with M-NT 1820 analog (without Cu) and sealed with a bath containing lithium polysilicate, GLYMO, DAMO, and 8-HQ showed minor pitting (<5 pits) and very minor white corrosion product.

[0126] Example 5 - Sealing Agent Composition, Its Application and Testing

[0127] To prepare a 700 g sealing agent bath, 0.35 g (0.050%) of a lauryl polyethylene glycol ether-based phosphate ester was stirred into 668.24 g of deionized water over 10 minutes. 10.41 g (1.49%) of lithium polysilicate (20%) was added to the solution, and the solution was stirred for 10 minutes. Then, 10.50 g (1.5%) of GLYMO (3-glycidoxypropyltrimethoxysilane) obtained from Evonik was added to the solution, and the solution was stirred for 30 minutes to ensure complete dissolution. 10.50 g (1.5%) of DAMO (N-2-aminoethyl-3-aminopropyltrimethoxysilane) obtained from Evonik was added to the solution, and the solution was stirred for 10 minutes (pH = 10.29). Table 9 below provides an overview of the components of the sealing agent composition.

[0128] Table 9

[0129]

[0130] Q-Lab AA2024-T3 aluminum plates (3”×10”×0.032”) were immersed in an aqueous alkaline degreaser bath (20% (v / v) and 60 °C C-AK 6849) for 15 minutes while continuously agitating. Then, the plates were immersed in a warm tap water rinse tank for 5 minutes, and then in an acidic deoxidizing bath (15% (v / v) C-IC 2310 + 25% (v / v) HNO3, at ambient temperature) for 5 minutes (etch rate of the cladding plate = 0.1 - 0.4 mils / surface / hour). After deoxidation, the plate was immersed in an ambient temperature tap water rinse tank for 2 minutes, and then immersed in an "Cr-free conversion coating" conversion coating containing M-NT 1820 (without copper additive; 3% (v / v); pH = 4.2 - 4.4; free fluoride = 50 ppm) with agitation by magnetic stirring at 300 rpm for 10 minutes at ambient temperature. After conversion coating, the plate was immersed in an ambient temperature deionized water rinse tank for 2 minutes, and then air dried for 10 minutes at ambient temperature. Next, the plate was immersed in the above-mentioned sealant bath with gentle agitation for 2 minutes at ambient temperature, then air dried at ambient temperature, and then subjected to performance evaluation.

[0131] After a 7-day (168-hour) neutral salt spray test (ASTM B117) according to MIL-DTL-81706B specification, the corrosion performance of the treated substrate was evaluated. The wet paint adhesion was evaluated according to MIL-DTL-81706B specification with test parameters obtained from reference FED-STD-141D (method 6301.3). The plates were coated with a chromate-based primer (MIL-PRF-23377K, type 1, class C2; 23377F12-GL) and / or a chromate-free primer (MIL-PRF-23377REV K, type 1, class N primer, epoxy high solids; 02GN084 Deft Light Aqua Green). Table 10 below provides the results of the corrosion performance evaluation for each tested sample.

[0132] Table 10

[0133] Sample Corrosion rating on AA2024 Adhesion rating on AA2024 6 No corrosion spots; almost no white corrosion products Negligible (almost no) paint peeling (Cr primer) 7 No corrosion spots; no white corrosion products Qualified (no paint peeling) (no Cr primer)

[0134] Example 6 - Sealant Composition and Its Application and Testing

[0135] To prepare a 700 g sealant bath, 0.31 g (0.044%) of lauryl polyglycol ether-based phosphate was stirred into 671.04 g of deionized water over 10 minutes. To this solution, 14.00 g (2.0%) of lithium polysilicate (20%) was added, and the solution was stirred for 10 minutes. Then, 11.65 g (1.66%) of GLYMO (3-glycidoxypropyltrimethoxysilane) obtained from Evonik was added to the solution, and the solution was stirred for 30 minutes to ensure complete dissolution. To this solution, 3.00 g (0.43%) of DAMO (N-2-aminoethyl-3-aminopropyltrimethoxysilane), and the solution was stirred for 10 minutes (pH = 10.60). Table 11 below provides an overview of the components of the sealant composition.

[0136] Table 11

[0137]

[0138] Q-Lab AA2024-T3, AA6061-T3, and AA7075-T6 aluminum plates (3”×10”×0.032”) were immersed in an aqueous alkaline degreaser bath (20% (v / v) and 60 °C C-AK 6849) with continuous agitation for 15 minutes. Then, the plates were immersed in a warm tap water rinse tank for 5 minutes, and then immersed in an acidic deoxidizing bath (15% (v / v) C-IC 2310 + 25% (v / v) HNO3, ambient temperature) for 5 minutes (etch rate of the clad plate = 0.1 - 0.4 mils / surface / hour). After deoxidation, the plates were immersed in an ambient tap water rinse tank for 2 minutes, and then immersed in a “Cr-free conversion coating” conversion coating containing M-NT 1820 (without copper additive; 3% (v / v); pH = 4.2 - 4.4; free fluoride = 50 ppm) with agitation at 300 rpm magnetic stirring for 10 minutes at ambient temperature. After conversion coating, the plates were immersed in an ambient deionized water rinse tank for 2 minutes and then air dried for 10 minutes at ambient temperature. Next, the plates were immersed in the above sealant bath with gentle agitation for 2 minutes at ambient temperature, then air dried at ambient temperature, and then subjected to performance evaluation.

[0139] After a 7-day (168-hour) neutral salt spray test (ASTM B117) according to MIL-DTL-81706B specification, the corrosion performance of the treated substrates was evaluated. The wet paint adhesion was evaluated according to reference FED-STD-141D (method 6301.3) for the MIL-DTL-81706B specification to obtain the test parameters. The plates were coated with a chromate-based primer (MIL-PRF-23377K, type 1, class C2; 23377F12-GL) and / or a chromate-free primer (MIL-PRF-23377REV K, type 1, class N primer, epoxy high solids; 02GN084 Deft Light Aqua Green). Table 12 below provides the results of the corrosion performance evaluation of each tested sample.

[0140] Table 12

[0141]

[0142] Example 7 - Glow Discharge Optical Emission Spectrometry (GD - OES)

[0143] Obtain GD - OES spectra for the following: (1) cleaned and de - oxygenated AA2024 aluminum alloy ( Figure 2 ); (2) cleaned and de - oxygenated AA2024 aluminum alloy treated for 10 minutes at ambient temperature with agitation by a “Cr - free conversion coating” conversion coating containing M - NT 1820 (without copper additive; 3% (v / v); pH = 4.2 - 4.4; free fluoride = 50 ppm) ( Figure 3 ); and the converted - coated samples immersed for 2 minutes at ambient temperature with agitation in the sealant baths according to Example 3 ( Figure 4 ), Example 3 ( Figure 5 ), Example 5 ( Figure 6 ), or Example 6 ( Figure 7 ), respectively.

[0144] Perform three pre - sputters (burns) on each of the samples, and collect the most representative GD - OES spectra. Plot the spectra showing aluminum (Al2), carbon (C2), lithium (Li×20), oxygen (O), silicon (Si2), and zirconium (Zr2). The GD - OES spectra obtained from repeated pre - sputters of individual samples show consistent and reproducible behavior in terms of layer thickness and elemental distribution. Minor variations in oxide thickness and slight differences in surface contaminants are typical variables seen in repeated pre - sputters.

[0145] Those skilled in the art will understand that the foregoing examples are merely illustrative embodiments of the components and properties of the present invention. They are in no way intended to limit the present invention to the exemplary embodiments.

Claims

1. A sealant composition for imparting corrosion resistance to a metal surface, the sealant composition comprising: Lithium polysilicate; A corrosion inhibitor; and An adhesion promoter; and Water; wherein the sealant composition is substantially free of chromium (VI).

2. The sealant composition according to claim 1, wherein, Based on the total weight of the composition, the lithium polysilicate is present in an amount of about 1-3% by weight.

3. The sealant composition according to claim 2, wherein, Based on the total weight of the composition, the lithium polysilicate is present in an amount of about 1.45-2.25% by weight.

4. The sealant composition according to claim 1, wherein the corrosion inhibitor comprises one or more of quinoline, organophosphates, azole-functional molecules, or any combination thereof.

5. The sealant composition according to claim 4, wherein the corrosion inhibitor comprises 8-hydroxyquinoline, organophosphates, salicylaldoxime, quinolinic acid, 1H-benzotriazole, tolyltriazole, methyl-1-H-benzotriazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, 5-amino-1,3,4-thiadiazole-2-thiol, L-cysteine, 5-aminotetrazole, 2-aminothiazole, or any combination thereof.

6. The sealant composition according to claim 4, wherein the corrosion inhibitor comprises 8-hydroxyquinoline.

7. The sealant composition according to claim 4, wherein the corrosion inhibitor comprises a C8-C 16 alkyl polyethylene glycol ether.

8. The sealant composition according to claim 4, wherein the corrosion inhibitor comprises a phosphate ester based on lauryl polyethylene glycol ether.

9. The sealant composition according to any one of claims 1-8, wherein the corrosion inhibitor is present in an amount of about 0.005% by weight based on the total weight of the composition to the solubility limit of the corrosion inhibitor in the sealant composition.

10. The sealant composition according to any one of claims 1-8, wherein the composition is alkaline.

11. The sealant composition according to any one of claims 1-8, wherein the adhesion promoter comprises an organo-functional alkoxysilane compound.

12. The sealant composition according to claim 11, wherein the adhesion promoter comprises an alkoxy functional group.

13. The sealant composition according to claim 12, wherein the adhesion promoter comprises an organo-functional group, the organo-functional group comprising an epoxy group, an epoxyalkyl group, an epoxyalkoxy group, an epoxyalkoxy group, an amino group, an aminoalkyl group, or an aminoalkylamino group, or any combination thereof.

14. The sealant composition according to claim 11, wherein the adhesion promoter comprises 3-glycidoxypropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, or 3-glycidoxypropyltrimethoxysilane and N-2-aminoethyl-3-aminopropyltrimethoxysilane.

15. The sealant composition according to any one of the preceding claims, wherein, Based on the total weight of the composition, the adhesion promoter is present in an amount of about 0.5-5% by weight.

16. The sealant composition according to any one of the preceding claims, further comprising a surfactant.

17. The sealant composition according to any one of the preceding claims, wherein the sealant composition does not contain any metal source other than the lithium polysilicate.

18. A method for protecting a metal surface from corrosion, the method comprising contacting the conversion-coated metal surface with a sealant composition according to any one of claims 1-17.

19. The method according to claim 18, wherein the conversion-coated metal surface is immersed in the sealant composition.

20. The method according to claim 18 or claim 19, wherein the conversion-coated metal surface is contacted with the sealant composition under ambient temperature conditions.

21. The method according to any one of claims 18-20, wherein the metal surface comprises aluminum or an aluminum alloy.

22. The method according to any one of claims 18-21, the method further comprising contacting the metal surface with a conversion coating composition before the step of contacting the metal surface with the sealant composition, wherein the conversion coating composition does not contain any chromium source.

23. The method according to claim 22, wherein the conversion coating composition comprises a Group IVB metal.

24. The method according to claim 23, wherein the conversion-coated metal surface comprises an oxide of a Group IVB metal.

25. The method according to claim 23 or 24, wherein the conversion coating comprises Zr, Ti, or Zr and Ti.

26. The method according to any one of claims 18-25, the method further comprising a step of deoxidizing the metal surface before the step of contacting the metal surface with the sealant composition.

27. The method according to claim 26, wherein the step of deoxidizing the metal surface is before contacting the metal surface with the conversion coating composition.

28. The method according to any one of claims 18-27, the method further comprising a step of degreasing the metal surface before the step of contacting the metal surface with the sealant composition.

29. The method according to claim 28, wherein the step of degreasing the metal surface is before the step of deoxidizing the metal surface and before contacting the metal surface with the conversion coating composition.

30. A metal component, the metal component comprising a surface that has been contacted with a sealant composition according to any one of claims 1-17.

31. The metal component according to claim 30, wherein the surface comprises aluminum or an aluminum alloy.

32. An article, the article comprising the metal component according to claim 30 or claim 31.

33. A manufactured article, the manufactured article comprising: a metal surface on which a conversion coating comprising a Group IVB metal is deposited; and a sealant layer comprising Li, Si, C, and O, wherein the sealant layer dries in situ on the conversion coating.

34. An article comprising a metal surface on which a sealant layer is deposited, wherein lithium is distributed in the sealant layer in an amount of about 2 - 7 mg / m as measured by glow discharge optical emission spectroscopy (GD - OES). 2 ​

Citation Information

Patent Citations

  • Permanganate based conversion coating compositions

    US20160083849A1

  • Trivalent chromium-containing composition for use in corrosion resistant coatings on metal surfaces

    US20170009330A1

  • Sealing Composition

    US20190316261A1